Interpretacija okolja na primeru Ljubljanskega barja - Erhartič, Bojan (Georitem, 2014)
The monograph treats an environmental interpretation which is not only one of the most effective processes for informing and raising the awareness of visitors to and residents of protected areas, but also one of the most demanding and complex ones. The case of the Ljubljana Moor (Ljubljansko barje) is used to analyze the relationship between people and nature from various perspectives and to present a possible approach to interpreting this cultural landscape. In 2008, the area was protected and designated the Ljubljansko barje Landscape park. A detailed analysis of the Iška River basin was performed in order to demonstrate how various interpretation tools can be used to interpret the environment for real and virtual visitors in various age groups.